The effect of a rating change announcement on bond price - Weinstein, Mark I. (Journal of Financial Economics, 1977)
This paper examines the behavior of corporate bond prices during the period surrounding the announcement of a rating change. We find some evidence of price change during the period from 18 to 7 months before the rating change is announced. We find no evidence of any reaction during the 6 months prior to the rating change. We also find little reaction, if any, during the month of the change or for 6 months after the change. This evidence contradicts the recent findings of Katz and Grier and Katz.